Percutaneous posterior full-endoscopic cervical foraminotomy and discectomy: a finite element analysis and radiological assessment. Issue 12 (9th September 2020) - Ke, Wencan; Zhi, Jinggang; Hua, Wenbin; Wang, Bingjin; Lu, Saideng; Fan, Lina; Li, Li; Yang, Cao
Abstract: Percutaneous posterior full-endoscopic cervical foraminotomy and discectomy (PECFD) is recognized as a safe, effective, and minimally invasive treatment for cervical spondylotic radiculopathy (CSR). However, the potential mechanisms of the degenerative changes and postoperative recurrence after PECFD are unclear. In this study, a finite element (FE) analysis and radiological assessment were performed to evaluate the biomechanical effects after PECFD. The FE model indicated that the ROM and IDP of C5–C6 increased significantly after PECFD in the extension loading. The radiological evaluation revealed that the extension ROM of C2–C7 and the operative level increased significantly at the one-year follow-up compared with that obtained preoperatively. Combining the FE results and radiological changes, we conclude that the increase in the ROM and IDP at the operative level in the extension loading is the potential cause of the degenerative changes and recurrences after PECFD surgery.